La sobreprotección de la familia y su incidencia en el comportamiento de los niños y niñas de primer año de educación general básica de la unidad educativa Francesco Riccati, de la ciudad de Quito. Periodo lectivo 2013-2014 - Cueva Robles, Elva del Carmen (2014)
This thesis refers to the " overprotection FAMILY AND ITS IMPACT ON THE BEHAVIOR OF CHILDREN FIRST YEAR BASIC EDUCATION GENERAL EDUCATION UNIT " FRANCESCO Riccati " QUITO CITY . LECTIVO PERIOD 2013-2014 " . It has been developed in accordance with the Rules of Graduation National University of Loja. In the present investigation the General Target raised was : Raising Parents on the impact that has on the behavior Overprotection of children and Girls High School , First Grade General Education Basic . The methods used in the preparation of this research work were : Scientist, Inductive, Deductive , Analytic , Synthetic , Descriptive and Statistical Model , which allowed for the discussion and comparison of the proposed variables. Applied to parents of children in the First Year of Basic General Education " Francesco Riccati " Educational Unit of Quito Poll: Two instruments were applied . Teaching period 2013 - 2014 to establish the Family Overprotection. Observation Form and applied to children children from First Year of Basic General Education “Francesco Riccati " Educational Unit of Quito . School period 2013-2014 to determine the behavior After analyzing the survey data applied to parents to set the Overprotection, one arrives at the following conclusion: 58% of parent’s surveyed family have not overprotect your child / ay 42% other. 63% of parents always Monitor when your child is playing , 57 % food gives your child in the mouth , 53% saw their child when they go to school , 38% Performs tasks school instead of his son ; and 34 % sleep with their son and daughter . According to the results of the implementation of the Monitoring tab is concluded that . 62% of children have not Aggressive behavior , Aggressive 31% ; and 7% Very Aggressive . 41% of children have a passive behavior , 37% No Passive Behavior ; and , 22% Very Passive behavior . 63% of boys and girls have investigated Very Assertive Behavior , 29% % Assertive Behavior ; and 9% Not Assertive Behavior .